Smart Last-mile Delivery Systems: Technological Advances, Operational Strategies, and Future Directions - Hussain, Mohammad Shadab; Shabana, Shabana; Bhaumik, Amiya; Duraipandi, Oyyappan; Ansari, Shoaib (International Review of Management and Marketing, 2026)
The rapid expansion of e-commerce and on-demand services has transformed last-mile delivery into one of the most critical, complex, and cost-intensive components of modern supply chains. Traditional delivery models are increasingly unable to cope with rising customer expectations, urban congestion, environmental pressures, and operational inefficiencies. In response, smart last-mile delivery systems based on digital technologies, automation, and data-driven optimization have emerged as a promising solution. This study provides a comprehensive and systematic review of the literature on smart last-mile delivery by integrating technological advances, operational strategies, and sustainability perspectives. Using a structured systematic literature review and bibliometric analysis of Scopus-indexed publications from 2000 to 2026, this research examines the evolution, intellectual structure, and thematic trends of the field. The analysis reveals a sharp growth in scholarly output after 2017, reflecting the increasing strategic importance of last-mile logistics in global e-commerce and urban freight systems. Keyword co-occurrence, thematic clustering, and network analysis show that the field is primarily anchored in e-commerce, logistics, and supply chain management, with last-mile delivery emerging as the dominant operational challenge. Strong linkages are also observed with sustainability, artificial intelligence, digital transformation, and urban logistics, indicating a shift toward technology-enabled and environmentally responsible delivery solutions. The findings further highlight the growing role of artificial intelligence, the Internet of Things, autonomous vehicles, drones, smart lockers, and micro-fulfilment centers in improving routing efficiency, reducing delivery failures, lowering costs, and mitigating environmental impacts. At the same time, the review identifies significant research gaps, particularly in relation to developing economies, long-term sustainability impacts, regulatory frameworks, and socio-economic consequences of automation. By offering an integrated synthesis of technological, operational, and sustainability dimensions, this study contributes to a deeper understanding of smart last-mile delivery systems and provides a roadmap for future research and policy. The results support the development of more resilient, efficient, and sustainable last-mile logistics models in the digital economy.